93.4k views
3 votes
Given this equation, find the answer

Given this equation, find the answer-example-1
User Cobaco
by
4.6k points

1 Answer

2 votes

Answer:

Explanation:

1

Because f(x) = --------

x - 4

1

f(x + h) = -------------

x + h - 4

and so:

1 1

----------- - -----------

f(x + h) - f(x) x+h - 4 x - 4 -h -1

------------------ = ------------------------------ = ------------------------ = ----------------------

h h h[x - 4][x + h - 4] [x - 4][x + h - 4]

User BVernon
by
5.4k points